Pendampingan Kader Pesantren Sebagai Aset Modal Sosial dalam Penguatan Moderasi Beragama - Wildani Hefni; Qurrotul Uyun (LP2M of Institute for Research and Community Services - UIN Walisongo, 2020)
Islamic boarding schools are an important element of education in Indonesia. Islamic boarding school educates students to understand and practice religion with a sense of tolerance and moderate. However, recently, the moderate nature of Indonesian Islam is challenged by the spirit of radicalism and conservatism Islam. In this context, this community service on mainstreaming religious moderation among students at Darus Sholah Islamic boarding school is very relevant to spread moderation and tolerant values in religious understanding. Strengthening religious moderatism among students at an Islamic boarding school is one of the strategies to prevent radicalism. Santri as a part of Islamic boarding schools plays an important role to build a social life in the process of socialization and internalization of socio-cultural values about harmony and peace as social capital. The result of this community service on strengthening religious moderatism among students of Islamic boarding schools will make the community of students at Islamic boarding school more aware and contribute to conveying religious understanding following the Islamic boarding school traditions. Pondok pesantren adalah satu elemen penting dalam dunia pendidikan di Indonesia. Pondok pesantren telah lama mengajarkan ilmu agama dengan nilai-nilai yang penuh toleransi dan moderat. Namun akhir-akhir ini, moderatisme Islam menghadapi tantangan dengan lahirnya pemahaman keislaman yang radikal dan konservatif. Dalam konteks ini, program pendampingan dan pemberdayaan kader pesantren di Darus Sholah menemukan relevansinya dengan tujuan untuk menguatkan serta menyebarluaskan pemahaman yang moderat dan toleran. Penguatan moderasi beragama dikalangan para santri merupakan salah satu strategi untuk mencegah lahirnya radikalisme. Santri sebagai bagian tak terpisahkan dari dunia pesantren memiliki peran yang cukup signifikan untuk menumbuhkan kehidupan sosial yang harmoni dan penuh dengan nilai perdamaian. Hasil dari pendampingan ini diharapkan dapat memberikan manfaat khususnya kepada para kader pesantren untuk lebih sigap dalam membumikan nilai-nilai pesantren yang moderat dan toleran.